PEMANFAATAN EKSTRAK KULIT BUAH PEPAYA (Carica Pepaya.L) PADA PRODUKSI VCO - Kamu, Vanda; Sangi, Meiske (CHEMISTRY PROGRESS, 2011)
ABSTRACTKamu, V. S, 2011. Utilization of pepaya rind extract in VCO production process.A research was done to determine optimum concentration of papaya rind extract in VCO (Virgin Coconut Oil)production process. Concentration of pepaya rind extracts were 10, 20 and 30% used in VCO productionprocess. VCO yield from the process were determine and purified with activated carbon and zeolite, thus storedfor 0, 1, 2, 3, and 4 weeks. Purified VCO were evaluated its moisture content and free fatty acid. Data wereanalyzed by ANOVA from two replication data by SPSS 15.0.The results show that optimum yield of VCO came from concentration of papaya rind extract 20% was 21,9 %.Purifying oil ((VCO) with adsorbent reduce moisture content and fre fatty acid content significantly, so oil quality(VCO) become better, and the best adsorbent is active carbon.Keywords : virgin coconut oil, papaya, moisture content, adsorbent